Cranioplasty: Review of Materials. Issue 8 (November 2016) - Zanotti, Bruno; Zingaretti, Nicola; Verlicchi, Angela; Robiony, Massimo; Alfieri, Alex; Parodi, Pier Camillo
Abstract : Abstract: Cranioplasty remains a difficult procedure for all craniofacial surgeons, particularly when concerning the reconstruction of large lacunae in the skull. Considering the significant clinical and economic impact of the procedure, the search for materials and strategies to provide more comfortable and reliable surgical procedures is one of the most important challenges faced by modern craniofacial medicine. The purpose of this study was to compare the available data regarding the safety and clinical efficacy of materials and techniques currently used for the reconstruction of the skull. Accordingly, the scientific databases were searched for the following keywords autologous bone, biomaterials, cranial reconstruction, cranioplasty, hydroxyapatite, polyetheretherketone, polymethylmethacrylate, and titanium. This literature review emphasizes the benefits and weaknesses of each considered material commonly used for cranioplasty, especially in terms of infectious complications, fractures, and morphological outcomes. As regards the latter, this appears to be very similar among the different materials when custom three-dimensional modeling is used for implant development, suggesting that this criterion is strongly influenced by implant design. However, the overall infection rate can vary from 0% to 30%, apparently dependent on the type of material used, likely in virtue of the wide variation in their chemico-physical composition. Among the different materials used for cranioplasty implants, synthetics such as polyetheretherketone, polymethylmethacrylate, and titanium show a higher primary tear resistance, whereas hydroxyapatite and autologous bone display good biomimetic properties, although the latter has been ascribed a variable reabsorption rate of between 3% and 50%. In short, all cranioplasty procedures and materials have their advantages and disadvantages, and none of the currently available materials meet the criteria required for an ideal implant. Hence, the choice of cranioplasty materials is still essentially reliant on the surgeon's preference.